MENJADI GURU PROFESIONAL (ISU DAN TANTANGAN MASA DEPAN) - Arifin, Zaenal (EDUTECH, 2014)
Abstract, Teaching it is an art because every teacher has their own style and characteristics. Therefore, every teacher has different styles and techniques in teaching. So is their performance, models, they ways they deliver the material, the use of methods and media as well as evaluation. In teaching, teachers are expected to not get stuck with the routine of traditional teaching (teacher-centered), which assumes that the learner is an "empty bottle" and must be filled with the knowledge as much as possible. The traditional concept of teaching has long been an issue in education, but in fact until now there are still many teachers who implement such methods at schools. The problem is how to change the paradigm of the teacher to become a professional teacher? How do teachers develop learning system in schools? How do they carry out effective learning? How to prepare teachers for the future? To address these problems, the writer tried to conduct a study of the literature and the results of relevant researches. To change the paradigm of teachers into professional teachers, then there are several requirements that must be met. First, teachers must have a minimum qualification and competence as a teacher candidate. In Indonesia, all teachers (kindergarten, elementary, junior high, high school or equivalent) should have at least relevant diploma (D.IV) or bachelor (S1) degree. Second, they have to understand the developmental level of students. Third, teachers must often be given the opportunity to attend training on the implementation of the curriculum and learning according to each level of education. Fourth, each semester, teachers are required to implement a learning model that can activate learners (student - centered) at school. This means each semester teachers use different learning model which is considered effective and relevant so that within one year there are two models of learning they strongly master in practice. Furthermore, to develop a learning system in schools, there are several things that must be mastered by teachers, among others: the development of strategies that should be considered including the mastery of a foreign language (at least in English) , the mastery of pedagogical competence and mastery of ICT (information and communication technology); learning (planning, implementation, and evaluation); organizing the class structure and routines; planning to achieve the objectives, outcomes and standards. To carry out an effective learning, teachers must be able to communicate effectively, use appropriate learning models, conduct classroom management ; use resources creatively, understand individual differences in learning, teach, values and moral education, work effectively with parents, as well as assessing and reporting objectively.Keywords: professional teacher, teacher-centered, student-centered, effective learning, learning systemÂ Abstrak. Mengajar itu adalah seni, karena setiap guru yang mengajar memiliki gaya dan karakteristik tersendiri. Karena itu, setiap guru mengajar memiliki gaya dan teknik yang berbeda. Begitu juga penampilan, model, cara menyampaikan materi, penggunaan metode dan media maupun evaluasi. Dalam mengajar, diharapkan guru tidak terjebak dengan rutinitas mengajar secara tradisional (teacher-centered), yang menganggap peserta didik itu adalah sebuah â€œbotol kosongâ€ dan harus diisi dengan pengetahuan sebanyak-banyaknya. Konsep mengajar yang tradisional ini sudah lama menjadi isu dalam dunia pendidikan, tetapi faktanya di sekolah, sampai sekarang masih banyak guru yang melaksanakan cara-cara seperti itu. Permasalahannya adalah bagaimana mengubahparadigma guru untuk menjadi guru yang profesional ? Bagaimana guru mengembangkan sistem pembelajaran di sekolah ? Bagaimana melaksanakan pembelajaran yang efektif ? Bagaimana mempersiapkan guru untuk masa yang akan datang ? Untuk menjawab permasalahan ini, penulis mencoba melakukan kajian dari berbagai literatur dan hasil penelitian yang relevan.Untuk mengubah paradigma guru menjadi guru yang profesional, maka ada beberapa syarat yang harus dipenuhi. Pertama, guru harus memiliki kualifikasi dan kompetensi minimal sebagai calon guru. Di Indonesia, semua guru (TK, SD, SMP, SMA dan yang sederajat) minimal harus D.IV atau S.1 (Sarjana) yang relevan. Kedua, memahami tingkat perkembangan siswa. Ketiga, guru harus sering diberi kesempatan untuk mengikuti pelatihan tentang implementasi kurikulum dan pembelajaran sesuai dengan jenjang pendidikannya masing-masing. Keempat, tiap semester, guru diwajibkan untuk menerapkan salah satu model pembelajaran yang dapat mengaktifkan peserta didik (child-centered) di sekolah. Artinya, setiap semester guru harus mengganti model pembelajaran yang dianggap efektif dan relevan, sehingga dalam waktu satu tahun ada dua model pembelajaran yang betul-betul dikuasai guru secara praktis. Selanjutnya, untuk mengembangkan sistem pembelajaran di sekolah, ada beberapa hal yang harus dikuasai guru, antara lain pengembangan strategi yang harus dipertimbangkan, yaitu penguasaan bahasa asing (minimal bahasa Inggris), penguasaan kompetensi pedagogi, dan penguasaan ICT (information and communication technology).pembelajaran (perencanaan, pelaksanaan, dan evaluasi); pengorganisasian struktur kelas dan rutinitas; perencanaan untuk mencapai tujuan, hasil dan standar. Untuk melaksanakan pembelajaran yang efektif, maka guru harus mampu berkomunikasi secara efektif; menggunakan model pembelajaran yang tepat; manajemen kelas; menggunakan sumber daya secara kreatif; memahami perbedaan individu dan belajar; mengajar, nilai, dan pendidikan moral; bekerja secara efektif bersama orang tua; serta melakukan penilaian dan pelaporan secara objektif. Untuk mempersiapkan guru pada masa yang akan datang, ada tiga halKata Kunci : guru profesional, techer-centered, student-centered, pembelajaran yang efektif, sistem pembelajaran